Defending Gallipoli : the turkish story - Broadbent, Harvey, 1947- (Melbourne University Publishing, 2015)
From the bestselling author of Gallipoli, The Fatal Shore comes this original, dramatic and eye-opening account of the infamous Gallipoli campaign, told through 'enemy eyes'. Based on exclusive access to Turkish archives, Defending Gallipoli reveals how the Turks reacted and defended Gallipoli. Author and Turkish language expert Harvey Broadbent spent five years translating everything from official records to soldiers' personal diaries and letters to unearth the Turkish story. It is chilling and revealing to see this famous battle in Australian history through the 'enemy' lens. The book comm.